Political, social build also religozny-spiritual conditions To Islam at the people of Arabian Peninsula (Journal of Philosophy Culture and Political Science, 2018)
To Islam the people of Arabian Peninsula had no religious outlook, political structure and unity in legal system. Variety of religious outlook and focus of a management system on rodoplemenny structure and influence of external forces as Byzantium, Syria and Sasanida influenced emergence of several independent educations in Arabian Peninsula. Coexistence of independent educations as Humerei in Yemen, Gassanita in Syria, Hira in Iraq, Kindi in Hadramuta and as, the independent cities as to Mecca, Medina, Tayf and other Arab tribes not subordinating each other, affected a sformirovaniye in Arabian Peninsula the shattered geopolitical situation. However, to Islam, in Mecca the organizations on protection of freedoms of people as Hilful-Fudul are  formed.